2017
DOI: 10.1002/acm2.12106
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the dosimetric leaf gap for use in planning VMAT treatments of spine SABR cases

Abstract: The dosimetric leaf gap (DLG) is a beam configuration parameter used in the Varian Eclipse treatment planning system, to model the effects of rounded MLC leaf ends. Measuring the DLG using the conventional sliding‐slit technique has been shown to be produce questionable results for some volumetric modulated arc therapy (VMAT) treatments. This study therefore investigated the use of radiochromic film measurements to optimize the DLG specifically for the purpose of producing accurate VMAT plans using a flattenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 22 publications
5
21
0
Order By: Relevance
“…Some studies have found good agreement between calculated and delivered doses by using the DLG measured with sweeping gap tests or the dynamic chair test . However, other authors found substantial discrepancies and reported on the need for tuning the DLG value configured in the Eclipse TPS. Kielar et al observed discrepancies between calculated and measured doses around 5% for the Varian's high‐definition multileaf collimator (HDMLC), which were greatly reduced by increasing the DLG entered into the TPS by more than 1 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found good agreement between calculated and delivered doses by using the DLG measured with sweeping gap tests or the dynamic chair test . However, other authors found substantial discrepancies and reported on the need for tuning the DLG value configured in the Eclipse TPS. Kielar et al observed discrepancies between calculated and measured doses around 5% for the Varian's high‐definition multileaf collimator (HDMLC), which were greatly reduced by increasing the DLG entered into the TPS by more than 1 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, volumetric modulated arc therapy (VMAT) has been explored and implemented to treat a variety of cancers including in the prostate, head and neck, lung, and spine 1, 2, 3, 4. VMAT is a dynamic treatment technique in which the radiation dose rates, gantry speeds, and movements of the multi‐leaf collimator and jaws are simultaneously varied while the beam is on 5.…”
Section: Introductionmentioning
confidence: 99%
“…The 3% ΔD criterion was selected in this study because it is widely used, in combination with a range of Δd values, but the use of 3% as a ΔD criterion is not universal. Similarly, GAI values of 100% and 95% were selected as examples of extreme and commonly‐used PSQA action levels, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Recent surveys suggested that 3%/3 mm are currently the most commonly used gamma evaluation criteria, and the AAPM's task group report on IMRT commissioning (TG‐119) used 3%/3 mm and the AAPM's more recent task group report on modulated radiotherapy quality assurance (TG‐218) recommended 3%/2 mm. Investigations of cranial and extra‐cranial stereotactic radiotherapy have reported the use of 3%/2 mm, 3%/1.5 mm, 3%/1 mm and 3%/0.3 mm criteria.…”
Section: Methodsmentioning
confidence: 99%